(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2010)
Drought-resistance of persimmon species and cultivars in the Ukrainian Forest-Steppe is studied. Morphological features of stomatal apparatus of leaves in relation to drought resistance are determined.